2022
DOI: 10.3390/ijerph19052991
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts among School-Attending Adolescents in Mongolia: Associated Factors and Gender Differences

Abstract: Attempting suicide is an important risk factor that can lead to suicide death. The aim of the current study was to examine the prevalence of suicide attempts and to identify the gender-specific predictors of suicide among adolescents in Mongolia. We analyzed data from the 2019 Mongolian Global School-Based Health Survey (GSHS) conducted nationwide among 13–18-year-old students. Univariable and multivariable analyses were performed to assess the correlates of suicide attempts. Overall, 32.1% of the adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
1
1
1
1
Order By: Relevance
“…Bullying was also linked to suicide attempts in this study, which is like other studies in Mongolia [ 33 ] and from 90 countries in a pooled analysis [ 15 ]. Students who are victims of bullying have low self-esteem and experience loneliness, distress, and mental health problems [ 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…Bullying was also linked to suicide attempts in this study, which is like other studies in Mongolia [ 33 ] and from 90 countries in a pooled analysis [ 15 ]. Students who are victims of bullying have low self-esteem and experience loneliness, distress, and mental health problems [ 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the current prevalence was lower than the previous studies done in Benin, Liberia, Guatemala, and Mongolia, which found the prevalence of suicidal attempts as 28.3%, 33.7%, 16.6% and 32.2% respectively [ 32 , 49 , 55 , 56 ]. The reason for this variation may be that in a study of Guatemala and Mongolia, there had been a greater number of female participants(more than 50%), but in the current study, females were lower than male participants 41.3%, and the risk of suicidal attempts was increased among female than males [ 57 ].…”
Section: Discussioncontrasting
confidence: 73%
“…Recent studies indicate that youth in Mongolia have been experiencing a concerning increase in mental health distress. In a recent study, 32.7% of adolescents ages 13–18 reported they had attempted suicide and they identified loneliness, bullying, and risky behaviors such as early sexual intercourse as key factors (Badarch et al, 2022). Further, death by suicide among adolescents increased from 3% to 11% between 2003 and 2019.…”
Section: Present Studymentioning
confidence: 99%